2004
DOI: 10.1364/ol.29.002893
|View full text |Cite
|
Sign up to set email alerts
|

Self-reconstruction of light filaments

Abstract: By observing how a light filament generated in water reconstructs itself after hitting a beam stopper in the presence and in the absence of a nonlinear medium, we describe the occurrence of an important linear contribution to reconstruction that is associated with the conical nature of the wave. A possible scenario by which conical wave components are generated inside the medium by the distributed stopper or reflector created by nonlinear losses or plasma is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 15 publications
3
39
0
Order By: Relevance
“…Consequently, filament represents a narrow, high-intensity central part of a GB beam, whose propagation losses are replenished from the low-intensity side lobes containing the main part of the beam's energy. This model is strongly supported by recent experimental and theoretical results [7,10,11] demonstrating extreme robustness (self-healing) of the filaments in reconstructing their intensity after encountering microscopic obstacles.In most of the studies reported so far filamentation was seeded using laser beams with Gaussian transverse profiles. Having in mind the GB nature of filaments, the possibility of directly launching a powerful Bessel beam into the material and thus circumventing the internal transformation from Gaussian toward GB beam, is intriguing.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Consequently, filament represents a narrow, high-intensity central part of a GB beam, whose propagation losses are replenished from the low-intensity side lobes containing the main part of the beam's energy. This model is strongly supported by recent experimental and theoretical results [7,10,11] demonstrating extreme robustness (self-healing) of the filaments in reconstructing their intensity after encountering microscopic obstacles.In most of the studies reported so far filamentation was seeded using laser beams with Gaussian transverse profiles. Having in mind the GB nature of filaments, the possibility of directly launching a powerful Bessel beam into the material and thus circumventing the internal transformation from Gaussian toward GB beam, is intriguing.…”
supporting
confidence: 68%
“…Consequently, filament represents a narrow, high-intensity central part of a GB beam, whose propagation losses are replenished from the low-intensity side lobes containing the main part of the beam's energy. This model is strongly supported by recent experimental and theoretical results [7,10,11] demonstrating extreme robustness (self-healing) of the filaments in reconstructing their intensity after encountering microscopic obstacles.…”
supporting
confidence: 68%
“…Nonlinear Xwaves [93,94] and O-waves [95] are named because of their evident X-like and O-like shapes, respectively, which appear in both the near-and the far-fields. Moreover, the interpretation of light filaments in the framework of conical waves readily explains the distinctive propagation features of light filaments such as the sub-diffractive propagation in the free space [83,92] and self-reconstruction after hitting physical obstacles [96][97][98], which are universal and regardless of the sign of material GVD, and which were verified experimentally as well. Therefore all subsequent features of the filament propagation in the regime of normal GVD, i.e.…”
Section: Conical Emissionmentioning
confidence: 54%
“…By contrast, blocked central spike (with beam stopper inside water cell) is quickly rebuilt by the energy flux from the beam periphery. Reconstruction effect was also observed in the linear propagation regime, i. e. outside the water cell, justifying the conical nature of spontaneously built wave [30]. Recent research in connection with air filaments has arrived to similar results, demonstrating self-reconstruction property of air filaments when colliding with water droplets [31], and immediate termination of filamentation process if the beam periphery is removed [32].…”
Section: Self-focusing Of Optical Wave Packetsmentioning
confidence: 56%